Preparation process of curcumin-loaded triterpenoid micromolecule co-assembly nanoparticles
By preparing curcumin-betaric acid-curcumin nanoparticles, the self-assembly and co-assembly capabilities of triterpene small molecule co-assembly are used to solve the problems of low bioavailability and unstable chemical properties of curcumin, and the wider application of curcumin in the food and medicine fields is achieved.
Patent Information
- Application Number
- CN202510077347.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-29
AI Technical Summary
The low bioavailability and unstable chemical properties of curcumin limit its application in the food field.
By screening the material composition ratio, curcumin-betaric acid-curcumin nanoparticles were prepared, and the self-assembly and co-assembly capabilities of triterpene small molecule co-assembly nanoparticles were used to improve the stability and bioavailability of curcumin.
It improves the water solubility, stability and bioavailability of curcumin, and expands its application scope in the food and medicine fields.
Smart Images

Figure CN119896324A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the fields of food science and nanotechnology, and particularly relates to a preparation process of curcumin-loaded triterpenoid small molecule co-assembly nanoparticles. Background Art
[0002] Curcumin is a polyphenolic ingredient derived from the rhizome of turmeric, which has multiple biological activities such as liver protection, nerve protection, anti-oxidation, antibacterial and anti-cancer. Natural curcumin can also be used as an antioxidant, flavoring agent and natural colorant in various foods and even cooking, becoming a substitute for synthetic additives. In addition, studies have shown that curcumin has little or no harm to the human body at high doses. Adding curcumin to food can not only enrich the taste of food, but also make the food have higher nutritional value.
[0003] However, curcumin itself has problems such as unstable chemical properties, poor water solubility and low bioavailability, which seriously limit its application in the food field. In order to solve this problem, researchers have developed many technical means. At present, the most concerned is the use of nanotechnology to improve the instability of curcumin itself. Now there are many delivery systems used for the encapsulation of curcumin, among which nanoparticles are considered to be a delivery system with great potential in improving the stability of active substances. In recent years, nanoparticles assembled from triterpenoid small molecules have attracted people's attention. Due to their unique assembly ability and physiological activities such as anti-inflammatory, antibacterial, immune protection and anti-cancer, triterpenoid small molecules are widely used as delivery materials.
[0004] Studies have found that triterpenoid small molecules with multiple physiological activities also have unique self-assembly and co-assembly capabilities, which makes them a natural material for encapsulating active substances, which can not only improve the biological activity of active substances, but also avoid harm to the body. Among the many triterpenoid small molecules, ursolic acid and betulinic acid are representatives of triterpenoid compounds. They not only have excellent antioxidant, anti-inflammatory and anti-cancer biological activities, but also their unique assembly ability makes them a drug delivery system for encapsulating curcumin. Therefore, the co-assembly system of curcumin encapsulated by ursolic acid and betulinic acid can not only improve the bioavailability of curcumin, but the material itself also has multiple activities. If added to food, it not only effectively overcomes the shortcomings of curcumin itself, but also gives the food a higher nutritional value. Summary of the invention
[0005] The purpose of the present invention is to solve the problems of low bioavailability and unstable chemical properties of polyphenol active substances such as curcumin, and to provide a preparation process of triterpenoid small molecule co-assembly nanoparticles loaded with curcumin by screening the composition ratio of materials, so as to expand the application range of active substances such as curcumin and make them have higher nutritional value in food.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] A preparation process of curcumin-loaded triterpenoid small molecule co-assembly nanoparticles, the process comprising:
[0008] Step 1: dissolving ursolic acid (UA) in dimethyl sulfoxide to prepare a solution of ursolic acid (UA) of a certain concentration;
[0009] Step 2: dissolving betulinic acid (BA) in dimethyl sulfoxide to prepare a betulinic acid (BA) solution of a certain concentration;
[0010] Step 3: dissolving curcumin (CCM) in dimethyl sulfoxide to prepare a curcumin (CCM) solution of a certain concentration;
[0011] Step 4: Mix the UA solution obtained in step 1 and the BA solution obtained in step 2 in an appropriate ratio;
[0012] Step 5: Mix the solution obtained in step 4 and the CCM solution obtained in step 3;
[0013] Step 6: ultrasonically subjecting the mixed solution obtained in step 5 to a certain period of time;
[0014] Step 7: The solution obtained in step 6 after ultrasonic treatment is centrifuged and washed with double distilled water for 3 to 5 times to obtain a precipitate, which is the prepared nanoparticles.
[0015] Furthermore, the solutions in steps 1 to 3 have a concentration of 30-35 mmol / L;
[0016] Further, the mixing ratio in step 4 is 0.6-4;
[0017] Further, in step 6, ultrasonication is performed at room temperature for 15-20 minutes;
[0018] Furthermore, the centrifugation conditions in step 7 are at 4°C, at a speed of 10000-12000 r / min, and for 15-25 min;
[0019] Furthermore, curcumin can be replaced by other polyphenol active substances such as resveratrol.
[0020] The beneficial effects of the present invention relative to the prior art are as follows: the material combination ratio in the present invention is fixed, and the water solubility and stability of the prepared ursolic acid-betulinic acid-curcumin nanoparticles are improved compared with free curcumin, and its bioavailability is effectively improved, providing more application scopes for curcumin in the fields of food and medicine. At the same time, the curcumin in the present invention can be replaced by other polyphenol active substances to improve its chemical properties and bioavailability. The method is simple to operate, and the prepared nanoparticles have uniform particle size, good water solubility, suitable drug loading, and good stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a scanning electron micrograph of the ursolic acid-betulinic acid nanoparticles (UA-BA NPs) in Example 1.
[0022] Figure 2 This is the scanning electron microscope image of UA-BA NPs in Example 2.
[0023] Figure 3 This is the scanning electron microscope image of UA-BA NPs in Example 3.
[0024] Figure 4 This is a scanning electron micrograph of the ursolic acid-betulinic acid-curcumin nanoparticles (UA-BA-CCM NPs) in Example 4.
[0025] Figure 5 This is the transmission electron microscopy image of UA-BA-CCM NPs in Example 4.
[0026] Figure 6 Scanning electron microscopy image of UA-BA-CCM NPs added with urea solution.
[0027] Figure 7 SEM images of UA-BA-CCM NPs added with SDS solution
[0028] Figure 8 Particle size distribution diagram of UA-BA NPs with different molar ratios.
[0029] Fig. 9 The particle size distribution diagram of different nanoparticles.
[0030] Fig.10 Zeta potential distribution diagram of UA-BA-CCM NPs.
[0031] Fig.11 Schematic diagram of the stability of different nanoparticles.
[0032] Fig.12 Three-phase contact angle images of free CCM and UA-BA-CCM NPs.
[0033] Fig.13 XRD diffraction pattern of UA-BA-CCM NPs.
[0034] Fig.14 Infrared spectrum of UA-BA-CCM NPs.
[0035] Fig.15 This is the UV absorption spectrum of UA-BA-CCM NPs.
[0036] Fig.16 This is the UV absorption spectrum of UA-BA-CCM NPs with urea added.
[0037] Fig.17 UV absorption spectrum of UA-BA-CCM NPs with SDS added.
[0038] Fig.18 Figure 2 shows the ABTS cation radical scavenging rate of UA-BA-CCM NPs.
[0039] Fig.19 This is the DPPH radical scavenging rate of UA-BA-CCM NPs.
[0040] Fig. 20 Release curves of free CCM and UA-BA-CCM NPs in the simulated gastrointestinal phase.
[0041] Fig.21 Release curves of free CCM and UA-BA-CCM NPs at pH 7.4.
[0042] Fig. 22 Release curves of free CCM and UA-BA-CCM NPs at pH 5.6.
[0043] Fig.23 Fluorescence images of 4T1 cells uptake of free CCM.
[0044] Fig.24 Fluorescence images of UA-BA-CCM NPs uptake by 4T1 cells.
[0045] Fig.25 Flow cytometric analysis of free CCM uptake by 4T1 cells.
[0046] Fig.26 Flow cytometric analysis of UA-BA-CCM NPs uptake by 4T1 cells. DETAILED DESCRIPTION
[0047] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention that does not depart from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0048] The nanoparticles obtained in the following examples were measured by scanning electron microscopy (SEM) and transmission electron microscopy (TEM); the particle size and Zeta potential were measured by dynamic laser light scattering (DLS); the drug loading and the release amount of the nanoparticles were measured by high performance liquid chromatography (HPLC); the free radical scavenging rate was measured by a microplate reader; the cellular uptake was observed by an inverted fluorescence microscope; the fluorescence intensity was determined by flow cytometry; the molecular structure of the nanocomplex was measured by X-ray diffractometer, Fourier transform infrared spectrometer (FTIR) and ultraviolet absorption spectrometer, and the actual assembly process was simulated by molecular dynamics simulation.
[0049] Example 1
[0050] The preparation method of ursolic acid-betulinic acid (UA-BA) nanoparticles with a molar ratio of 1 in this embodiment is as follows:
[0051] (1) Take ursolic acid (UA) and betulinic acid (BA) separately and dissolve them in DMSO solution.
[0052] (2) Mix with distilled water in a ratio of 3:3 and sonicate for 10 min.
[0053] (3) The sonicated solution was centrifuged at 4°C and 10,000 r / min for 20 min, and the resulting precipitate was ursolic acid-betulinic acid (UA-BA) nanoparticles with a molar ratio of 1.
[0054] Example 2
[0055] The preparation method of UA-BA nanoparticles with a molar ratio greater than 1 in this example is basically the same as that in Example 1, except that the amount of ursolic acid added is increased to 4 times that of betulinic acid.
[0056] Example 3
[0057] The preparation method of UA-BA nanoparticles with a molar ratio of less than 1 in this example is basically the same as that in Example 1, except that the amount of ursolic acid added is reduced to 2 / 3 of that of betulinic acid.
[0058] Example 4
[0059] The preparation method of composite nanoparticles loaded with curcumin in this embodiment:
[0060] Ursolic acid (UA) and betulinic acid (BA) were dissolved in DMSO solution, and curcumin (CCM) was weighed and dissolved in DMSO. A 3:3 mixture of UA-BA and CCM was added to distilled water, and the precipitate obtained after centrifugation was UA-BA-CCM NPs. The morphology of the prepared nanoparticles is shown in Figure 4 As shown, it presents a good spherical morphology.
[0061] Example 5
[0062] This embodiment is to prepare a free curcumin solution, and the preparation method is as follows:
[0063] Weigh curcumin and dissolve it in DMSO solution to prepare a 30 mmol / L curcumin solution.
[0064] Inspection and testing
[0065] The experimental indicators of each substance in Examples 1-5 were measured, and the main measurement methods are as follows:
[0066] Test 1: Scanning Electron Microscope (SEM) Test
[0067] The nanoparticle solution obtained in Example 1-4 was naturally evaporated and dried, and then the sample was made into a sheet and attached to the conductive adhesive. After gold spraying, the surface morphology of the nanoparticles was recorded by Quanta 200FEG SEM spectrometer at 20kV, 10ma, SE mode and spot size 3.5. The results are as follows: Figure 1-4 shown.
[0068] Depend on Figure 1-3 It can be observed that the ursolic acid-betulinic acid nanoparticles (UA-BA NPs) with a molar ratio of 1 exhibited a better spherical morphology, and the particle size was less than 200 nm.
[0069] Experiment 2: Dynamic Light Scattering (DLS) Test
[0070] The nanoparticle dispersions obtained in Examples 1-4 were placed in a specific container, and the particle size distribution and surface potential of the nanoparticles were measured by dynamic light scattering using a nanoparticle size and zeta potential analyzer. Figure 8 As shown; the particle size distribution of loaded curcumin is shown as Fig. 9 The absolute value of the Zeta potential represents the stability of the nanoparticles. Fig.10 shown. Fig.11 Presented are the particle sizes of UA-BA-CCM NPs with different ratios dispersed in aqueous solution for 14 days.
[0071] Depend on Figure 8From the particle size distribution diagram, it can be observed that the UA-BA NPs with a molar ratio of 1 have a particle size less than 200 nm and have good monodispersity. Fig. 9 It can be seen that the particle size of UA-BA-CCM NPs is 222.6nm. Fig.10 The Zeta potential diagram shows that the nanoparticles also have good stability. At the same time, the particle size changes of UA-BA-CCM NPs with different ratios uniformly dispersed in water for 14 days show that UA-BA-CCM NPs with a molar ratio of 1 have excellent stability, so the optimal ratio of UA and BA is a molar ratio of 1.
[0072] Experiment 3: Transmission Electron Microscope (TEM) Test
[0073] The samples were deposited on a copper grid with a carbon film (300 mesh), dried, and then the microstructure of the samples was observed using a Tecnai G2 F30 FEI transmission electron microscope.
[0074] from Figure 5 It was observed that UA-BA-CCM NPs exhibited a spherical shape with a solid structure. In addition, UA-BA-CCM NPs had a uniform structure with consistent particle size and no aggregation.
[0075] Test 4: Determination of water solubility
[0076] The three-phase contact angle can reflect the hydrophilicity of the material. The freeze-dried powder of the nanoparticles was redissolved in distilled water and dropped on a glass slide. After the droplet was completely dry, a drop of distilled water was added to the dry surface of the sample. After balancing for 10-15 seconds, the droplet was photographed with a high-speed camera. The contour of the imaged droplet was simulated and calculated to obtain the three-phase contact angle.
[0077] The three-phase contact angle of nanoparticles is Fig.12 As shown. The size of θ reflects the hydrophilicity of the material, and θ < 90° is a hydrophilic surface. Fig.12 From the schematic diagram of the three-phase contact angle, it can be observed that the water solubility of UA-BA-CCM NPs is significantly improved compared with that of free curcumin.
[0078] Experiment 5: X-ray diffraction test
[0079] exist Fig.13In the results, Free UA, free BA and free CCM are highly crystalline structures. Their characteristic peaks disappeared in the diffraction pattern of UA-BA-CCM NPs. This phenomenon may be caused by hydrogen bonding. The hydrogen bonding interaction formed during the molecular assembly process destroys the intrinsic structure of the molecules, resulting in the disappearance of the characteristic peaks, thereby driving the three molecules to arrange and assemble in a specific manner. The original crystal structure was destroyed and did not provide enough energy to form an ordered crystal structure, resulting in the disappearance of the characteristic peaks in the spectrum of UA-BA-CCM NPs. The results show that CCM was successfully loaded and exists in an amorphous form. In addition, a large number of hydrophilic groups are exposed on the surface of the nanoparticles, enhancing their hydrophilicity. The change in the three-phase contact angle of the nanoparticles proves this speculation ( Fig.13 )
[0080] Experiment 6: Fourier transform infrared spectroscopy test
[0081] We measured the infrared spectra of different nanoparticles and analyzed the main mechanism of their loading of CCM. The infrared spectra of the four nanoparticles and the physical powders of UA, BA and CCM are shown in Figure 2. Fig.14 As shown. When hydrogen bonds are formed or strengthened, the vibration bands usually shift to higher wavelengths or lower wavenumbers. The OH absorption peaks of Free UA and BA are both close to 3440 cm-1. The sharp peak at 3509 cm-1 represents phenol-OH in the CCM infrared spectrum. The OH characteristic peaks in the nanoparticle spectrum shift to lower wavenumbers, indicating the strengthening of hydrogen bonding interactions ( Fig.14 ). This indicates that during the assembly process of UA, BA and CCM, new hydrogen bonding interactions were formed, resulting in an increase in the strength of hydrogen bonds. The infrared spectrum of CCM has no characteristic peaks at 1877-1650cm-1. However, in the infrared spectrum of UA-BA-CCM NPs, a new characteristic peak appeared at 1692cm-1 ( Fig.14 ), indicating that CCM interacted with UA and BA.
[0082] Test 7: UV absorption spectrum test
[0083] exist Fig.15 In the experiment, the UV absorption peak of free CCM was 437nm, while the UV absorption peak of co-assembled CCM increased to 443nm. We speculated that the presence of hydrophobic interactions and hydrogen bonds between molecules may affect the UV absorption wavelength. Therefore, urea was added to the sample to observe whether hydrogen bonds were formed. After adding urea, the characteristic UV absorption peak of CCM decreased to 407nm ( Fig.16 ), the morphology of the nanoparticles also changed significantly ( Figure 6). It shows that hydrogen bonds are formed during the assembly of the three molecules, and the addition of urea breaks the hydrogen bonds, resulting in a shortening of the wavelength, shifting toward the absorption wavelength of free curcumin. At the same time, SDS was added to the nanoparticles to determine the presence of hydrophobic interactions. Fig.17 It shows that after adding SDS, the characteristic UV absorption peak of CCM changes from 443nm to 406nm, and the morphology of nanoparticles changes from spherical to irregular ( Figure 7 ), indicating that hydrophobic interactions do exist during the assembly process. Through infrared and ultraviolet spectroscopy experiments, it was preliminarily verified that hydrogen bonds and hydrophobic interactions are the main forces. When urea and SDS solutions were added, the two forces were destroyed, the morphology of the nanoparticles changed, and the wavelength of the ultraviolet absorption spectrum shifted, which once again verified the existence of the two forces and drove the molecules to combine.
[0084] Test 8. Evaluation of Antioxidant Activity
[0085] (1) ABTS cation radical scavenging rate
[0086] Mix the ABTS reaction solution and 100 μL sample solution, shake and react at room temperature in the dark for 6 minutes, and then measure the absorbance A1 at 734 nm. Replace the sample solution with anhydrous ethanol to measure the absorbance A2. Calculate the ABTS free radical scavenging rate of the sample to be tested (three parallels per group), the formula is as follows:
[0087]
[0088] In the formula, A1 is the absorbance of the sample and A2 is the absorbance of the anhydrous ethanol mixture.
[0089] (2) DPPH free radical scavenging rate
[0090] Take each sample solution to be tested and add DPPH solution at the same time. After the reaction is protected from light for 40 minutes, use a microplate reader to detect its absorbance at 517nm, which is recorded as A1. Use anhydrous ethanol to replace the sample solution to record the absorbance, which is recorded as A0; use anhydrous ethanol to replace the DPPH solution to record the absorbance, which is recorded as A2. The DPPH free radical scavenging rate of the sample to be tested is calculated by the formula as follows:
[0091]
[0092] In the formula, A0 is the absorbance of the sample solution replaced by anhydrous ethanol, A1 is the absorbance of the sample, and A2 is the absorbance of the DPPH solution replaced by anhydrous ethanol.
[0093] ABTS cation radical scavenging rate and DPPH free radical scavenging rate Fig.18 and Fig.19As shown in the figure, it can be seen that both the ABTS cation radical scavenging rate and the DPPH radical scavenging rate are the most effective of UA-BA-CCM NPs, which are significantly higher than the free curcumin, and the scavenging rates of the nanoparticles placed for 7 days and the fresh nanoparticles are slightly different, indicating that the encapsulated curcumin not only has better free radical scavenging ability than the free curcumin but also has good stability.
[0094] Test 9: Simulated Gastrointestinal Release Analysis
[0095] The freeze-dried nanoparticles were dispersed in SGF and transferred to a dialysis membrane bag. The temperature was 37°C, the mechanical stirring speed was 50-100r / min, and 20-50μL of sample was taken out from the dialysis bag at regular intervals and replenished with solution. The concentration of curcumin in the sample was determined by Agilent 1100 HPLC. The release curve over time was plotted.
[0096] Each gastric / intestinal phase sampling requires the addition of an equal amount of gastric or intestinal phase solution to meet the sink conditions. The cumulative release (E) is calculated by the following equation:
[0097]
[0098] Where, E (%) is the cumulative release percentage of curcumin. V0 (mL) is the volume of simulated gastric or intestinal fluid supplemented. n (μg / mL) is the curcumin concentration at the nth time. e (mL) is the volume of each sample pipetted. M0 (μg) is the total amount of curcumin.
[0099] Fig. 20 It is an in vitro simulated gastrointestinal phase release profile, and curcumin is usually absorbed in the small intestine. Fig. 20 The results showed that freeCCM was rapidly released to 48% after about 40 minutes in the simulated gastric phase, while UA-BA-CCM NPs were only released to 56% after 105 minutes in the simulated gastric phase. After entering the simulated intestinal phase, UA-BA-CCM NPs achieved 96% release, as did free CCM ( Fig. 20 ). The results showed that UA-BA-CCM NPs were less affected by digestive juices in the simulated gastric phase compared to free CCM. This may be due to the fact that curcumin was encapsulated inside during the assembly process, which effectively reduced the effect of gastric digestive juices on curcumin. In addition, the nanoparticle delivery system can act as a protective shield for curcumin, avoiding the early release of curcumin and improving the bioavailability of curcumin.
[0100] Experiment 10: Kinetic Analysis of Nanoparticle Release in Simulated Gastrointestinal Phase
[0101] Four commonly used kinetic models (Turkes & Acikel, 2024) were used to analyze the CCM release curve. The predicted values in the kinetic release model were fitted to the CCM release curve, and the determination coefficient (R 2 ) to determine the goodness of fit.
[0102] Zero-order model: M t / M ∞ =kt
[0103] First-order model: M t / M ∞ =1-e -kt
[0104] Higuchi Model: M t / M ∞ =kt 1 / 2
[0105] Ritger-Peppas Model: M t / M ∞ =kt n
[0106] Among them, M t and M ∞ They represent the amount of CCM released at a certain time and equilibrium, respectively. n represents the diffusion index: fickian diffusion is n<0.43; irregular release is 0.43n<0.85; and corrosion release is n>0.85.
[0107] The drug release process is complex and cannot be explained by a single kinetic model. The zero-order model, first-order model, Higuchi model, and Ritger-Peppas model were used to analyze the release profiles of the nanoparticles. The release profiles of the nanoparticles and free CCM were best fitted by the first-order model with the highest correlation coefficient, followed by the Higuchi model. When fitted with the Ritger-Peppas model, diffusion exponent (n) values ranging from 0.6 to 0.7 were observed, indicating irregular diffusion. The irregular release observed in the experiment may be due to the change in the surface charge of the particles during the release process.
[0108] Experiment 11: Release analysis under different pH conditions
[0109] The freeze-dried nanoparticles were dispersed in 2 ml of dispersion medium and transferred to a dialysis membrane bag (MWCO = 3500 Da). 500 mL of PBS (pH 7.4 and 5.6) containing 1 mol / L sodium salicylate solution was added at 37 °C and 70 r / min. 20 μL of sample was taken out from the dialysis bag at regular intervals and the solution was replenished. The concentration of curcumin (CCM) in the sample was determined by Agilent 1100 HPLC.
[0110] pH 7.4 is the physiological environment, and pH 5.6 is the microenvironment of tumor cells. The release rates of free curcumin (CCM) and nanoparticles within 1.5 hours after entering the simulated physiological environment were both within 30%, and the release of free CCM reached 70% after 1.5 hours ( Fig.21 On the other hand, UA-BA-CCM NPs began to rapidly release up to 40% after 2 h, further indicating that the stability of the UA-BA-CCMNPs delivery system was superior to that of free CCM. In addition, the nanoparticles rapidly released up to 42% 2.5 h after entering the simulated cell microenvironment. In contrast, free CCM rapidly released up to 64% ( Fig. 22 ). In addition, the highest fitting parameters of the release curves of freeCCM in different physiological environments corresponded to the first-order model. In contrast, the highest fitting parameters of the release curves of nanoparticles in different physiological environments corresponded to the Ritger-Peppas model. The difference in the appropriate fitting curves may be attributed to the unique assembly structure of the nanoparticles, with UA in the outermost layer. This special structure can improve the stability and bioavailability of curcumin.
[0111] Experiment 12: Cellular uptake and flow cytometry
[0112] Fig.23 and Fig.24 The cell uptake of free curcumin (CCM) and UA-BA-CCMNPs was observed by fluorescence inverted microscopy. The cell uptake time was recorded at 5 min, 0.5 h, and 3 h, respectively. Fig.23 As can be seen from the figure, freeCCM showed obvious fluorescence signals only at 3h. In addition, the quantitative analysis results of flow cytometry are shown in Figure 25-26 As shown. The fluorescence intensity of Free CCM was 1014, while that of UA-BA-CCM NPs was 1135. Compared with free CCM, cells incubated with UA-BA-CCM NPs showed higher fluorescence intensity. In particular, after 3h of incubation, the cell fluorescence intensity was significantly enhanced to 8182.
[0113] Due to electrostatic and hydrophobic interactions, lipid-soluble free CCM resists proteins on the cell membrane. This results in low or no cellular uptake of free CCM, thereby reducing the utilization of CCM in vivo. In contrast, UA-BA-CCM NPs showed a significant fluorescence signal at 0.5 h ( Fig.25), indicating that the special structure of UA-BA-CCM NPs is easily bound by the cell membrane structure. This phenomenon may be related to the negative charge on the particle surface and its uniform nanosize. Negatively charged particles adsorb to positively charged sites through electrostatic interactions. After local neutralization of the potential, membrane bending occurs, which promotes cellular uptake. In addition, nanoparticles that have been bound to the membrane surface show a lower charge density, which further promotes the adsorption of other free particles. Therefore, UA-BA-CCM NPs can improve the utilization of curcumin.
[0114] The present invention belongs to the field of food science and nanotechnology. The present invention utilizes the co-assembly ability of the material itself, and prepares a triterpenoid small molecule co-assembly nanoparticle loaded with curcumin having a good spherical morphology and a suitable size by screening the material combination ratio. By embedding the active substance, its stability, antioxidant ability and bioavailability are significantly improved, and the loading amount can reach 20.42%. And the preparation method of the present invention is simple and convenient. In addition, compared with free curcumin, water solubility, stability and antioxidant activity are improved, and bioavailability is improved, and it can be widely used in food and medicine fields.
Claims
1. The present invention is a process for preparing curcumin-loaded triterpenoid small molecule co-assembly nanoparticles, the steps of which are as follows: Step 1: Dissolve ursolic acid (UA) in dimethyl sulfoxide to prepare a certain concentration of ursolic acid (UA) solution. Step 2: dissolve betulic acid (BA) in dimethyl sulfoxide to prepare a betulic acid (BA) solution of a certain concentration. Step 3: Dissolve curcumin (CCM) in dimethyl sulfoxide to prepare a curcumin (CCM) solution of a certain concentration. Step 4: Mix the UA solution obtained in step 1 and the BA solution obtained in step 2 in an appropriate ratio. Step 5: Mix the solution obtained in step 4 and the CCM solution obtained in step 3. Step 6: Ultrasonicate the mixed solution obtained in step 5 for a period of time. Step 7: The solution obtained in step 6 after ultrasonic treatment is centrifuged and washed with double distilled water for 3-5 times to obtain a precipitate, which is the prepared nanoparticles.
2. The preparation process of a curcumin-loaded triterpenoid small molecule co-assembly nanoparticle according to claim 1, characterized in that The solutions described in steps 1 to 3 have a concentration of 30-35 mmol / L.
3. The preparation process of a curcumin-loaded triterpenoid small molecule co-assembly nanoparticle according to claim 1, characterized in that The mixing ratio in step 4 is 0.6-4.
4. The preparation process of a curcumin-loaded triterpenoid small molecule co-assembly nanoparticle according to claim 1, characterized in that In step 6, ultrasonication was performed for 15-20 min at room temperature.
5. The preparation process of a curcumin-loaded triterpenoid small molecule co-assembly nanoparticle according to claim 1, characterized in that The centrifugation conditions in step 7 are: at 4°C, with a rotation speed of 10000-12000 r / min and centrifugation for 15-25 min.
6. The process for preparing a curcumin-loaded triterpenoid small molecule co-assembly nanoparticle according to claim 1, characterized in that Curcumin can be replaced with other polyphenolic active substances such as resveratrol.